’PERFORMANCE SCOLAIRE AUX EXAMENS D’ETAT EN VILLE DE GOMA, RDC: QUELLE DIFFERENCE ENTRE LE PUBLIC ET LE PRIVE ?’ - Ghislain KUMBUKA KALIHOFU (IJRDO- Journal of Educational Research, 2020)
This article[1] is of particular interest: the performance of the school. Education in the DRC in general and in Goma in particular in the days before independence was effective. Over time, this teaching has lost some of its performance qualities. In addition to taking over the teaching from parents, there is a multiplicity of schools as well as small and medium-sized enterprises. Performance monitoring has escaped the authority while located there. By approaching this subject, we want to know if there is a difference in performance between private and public schools in the city of Goma, to determine the factors and make proposals to make schools more efficient. This analysis first requires the concept of efficiency of education systems through their performance in terms of retention, flow and success in the production of outputs. This performance was measured by "the results", from the effects obtained by the finalist students in the tests and particularly in the State examinations of the 2011, 2012, 2013 and 2014 editions. [1] This article is the enriched version of our unpublished dissertation of license in Administation and Planning of Education. He had made a comparative analysis of the performances of private and public sclools in the pedagogical section, City of Goma, DRC, in July 2015 at the Adventist University of Goma.